The Influence of Internal Heat Exchanger on the Performance of Transcritical CO2 Water Source Heat Pump Water Heater - Fan Feng; Ze Zhang; Xiufang Liu; Changhai Liu; Yu Hou (Energies, 2020)
The characteristics of the transcritical CO2 heat pump water heater (HPWH) system are; a lower inlet hot water temperature (Ti-hw) (sometimes this is lower than the water source temperature), and an outlet gas cooler temperature (To-gc) which is affected by the Ti-hw and often lower than the critical temperature. In order to study the effects of the internal heat exchanger (IHX) on the operational performance of the transcritical CO2 HPWH when To-gc is low, a transcritical CO2 water source HPWH experiment platform is established to conduct experimental research and comparative analysis on the operational performance of the transcritical CO2 water source HPWH, with or without IHX. It is found that, if only the coefficient of performance (COP) and heating at the optimal exhaust pressure of the transcritical CO2 water source HPWH were considered, COP and the heating of the non-IHX system would be slightly higher than those of the IHX system at the lower hot water flow and water source temperature, and this increase was not obvious. At the higher hot water flow rate and water source temperature, COP and the heating of the non-IHX system were also higher than those of the IHX system, and the increase was obvious. The experiment results showed that, near the optimal exhaust pressure, the variation range of COP and heating of the IHX system is relatively small, and the system has a relatively high stability.